2015
DOI: 10.1080/14763141.2015.1084034
|View full text |Cite
|
Sign up to set email alerts
|

Shooting motion in high school, collegiate, and professional men’s lacrosse players

Abstract: The purposes of this research were to quantify the kinematics of the lacrosse shot, based on arm dominance and player experience level. Male players (N = 39; 14–30 years; high school [n = 24], collegiate [n = 9], professional [n = 6]), performed overhead shots using dominant and non-dominant sides. Motion was captured using a high-speed, 12-camera optical system and high-speed filming. Body segment rotational velocities and joint angles were determined at key points in the shot cycle from foot contact (0% of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Mercer and Nielson 20 provided a detailed description of multiple phases of a lacrosse shot that has been simplified in our recent work. 30 Key phases related to the lacrosse shot were selected due to reliable reproduction in our motion analysis. Still images of these phases and the respective events are depicted in Figure 1 , A and B .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercer and Nielson 20 provided a detailed description of multiple phases of a lacrosse shot that has been simplified in our recent work. 30 Key phases related to the lacrosse shot were selected due to reliable reproduction in our motion analysis. Still images of these phases and the respective events are depicted in Figure 1 , A and B .…”
Section: Methodsmentioning
confidence: 99%
“…The details of this technique have been previously described. 30 Data were captured at 200 Hz. Reflective markers were applied to the following anatomical landmarks: right scapula (offset), acromion processes, lateral epicondyles of the elbow, midway between the ulnar and radial styloid processes, third metacarpal, posterior superior iliac spines, anterior superior iliac spines, greater trochanters, lateral femoral epicondyles, lateral malleoli, heels, and the hallux.…”
Section: Methodsmentioning
confidence: 99%
“…This finding may be linked to the important technical skill of overhand lacrosse shooting. During this skill when shooting right-handed the left leg is stepped forward then planted into the ground during the stick acceleration phase and contributes to force production through a powerful hip extension [20]. Previous research has demonstrated that the biceps femoris muscle significantly contributes to force production during execution of an overhand lacrosse shot and that the activation of the muscle increases concomitantly with shot speed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen reflective markers were applied bilaterally at the lateral tip of the acromion, lateral humeral epicondyle, greater trochanter, lateral femoral epicondyle, lateral malleolus, and hallux; additional markers were placed on the radial and ulnar styloid processes of the dominant hand with one marker placed on the non-dominant radioulnar joint. 26,28 Reflective tape was placed on a standard NCAA collegiate ball. Each player was instructed warm-up based on their standard team regulated stretching and throwing preparation routine.…”
Section: Pitch Biomechanics Preparationmentioning
confidence: 99%